Digitalization of Ancient Sculpting Models and 3D Design Using Photogrammetry Methodology - Dovramadjiev, Tihomir (International Journal of Engineering and Management Sciences, 2019)
The digitization of ancient sculptures is particularly relevant and necessary in relation to the preservation of the cultural heritage. And the studied ancient models have their unique identity in terms of their visual and functional qualities. In parallel, the study aims to optimize the technological process related to photogrammetric measurements and calculations, technological tools and specialized software applications such as Autodesk ReCap, Blender and MeshMixer. The used models in the article are for re-presentation of popular ancient models & artifacts from city of Varna (by the ancient name Odessos). By using a 3D print device, one of the resulting digitized models of an ancient angel will materialize by applying specific techniques to redesign its geometry. The completed 3D printed item of re-designed model of ancient stone angel is only for personal and non-comercial use. One of the main point in the article is to show advanced computer techniques for teaching and studying. The information in this article has been built for helping other specialist working in digital field regarding photogrammetry. Also the material can be useful for designers, engineers, archaeologists and others in their work for the publicity of ancient treasures.